Flexible Large-Area Graphene Films of 50–600 nm Thickness with High Carrier Mobility - Luo, Shiyu; Peng, Li; Xie, Yangsu; Cao, Xiaoxue; Wang, Xiao; Liu, Xiaoting; Chen, Tingting; Han, Zhanpo; Fan, Peidong; Sun, Haiyan; Shen, Ying; Guo, Fan; et al. (Nano-Micro Letters, 2023)
Bulk graphene nanofilms feature fast electronic and phonon transport in combination with strong light–matter interaction and thus have great potential for versatile applications, spanning from photonic, electronic, and optoelectronic devices to charge-stripping and electromagnetic shielding, etc. However, large-area flexible close-stacked graphene nanofilms with a wide thickness range have yet to be reported. Here, we report a polyacrylonitrile-assisted ‘substrate replacement’ strategy to fabricate large-area free-standing graphene oxide/polyacrylonitrile nanofilms (lateral size 20 cm). Linear polyacrylonitrile chains-derived nanochannels promote the escape of gases and enable macro-assembled graphene nanofilms (nMAGs) of 50–600 nm thickness following heat treatment at 3,000 °C. The uniform nMAGs exhibit 802–1,540 cm2 V−1 s−1 carrier mobility, 4.3–4.7 ps carrier lifetime, and > 1,581 W m−1 K−1 thermal conductivity (nMAG-assembled 10 µm-thick films, mMAGs). nMAGs are highly flexible and show no structure damage even after 1.0 × 105 cycles of folding–unfolding. Furthermore, nMAGs broaden the detection region of graphene/silicon heterojunction from near-infrared to mid-infrared and demonstrate higher absolute electromagnetic interference (EMI) shielding effectiveness than state-of-the-art EMI materials of the same thickness. These results are expected to lead to the broad applications of such bulk nanofilms, especially as micro/nanoelectronic and optoelectronic platforms. Highlights: 1 Large-area production of self-standing graphene nanofilm ( 20 cm) through a clean ‘substrate replacement’ strategy. 2 Realizing highly crystalline graphene nanofilms without micro-gasbags by introducing polymers. 3 The graphene nanofilms demonstrate a solid light–matter interaction (photoelectric conversion in the mid-infrared and electromagnetic interference (EMI) shielding in X-band) with performance beyond state-of-the-art graphene/silicon diodes and EMI materials.